ISDC Review of 2025-2030 Research & Innovation Portfolio Proposals - CGIAR Independent Science for Development Council (2024)
The Independent Science for Development Council (ISDC) reviewed the proposals forming the CGIAR 2025-2030 Science and Innovation Portfolio (Portfolio), submitted to the ISDC Secretariat by CGIAR Leadership on 27 September 2024. The external review of the proposals is an essential part of good governance and quality assurance, delivering benefits to CGIAR researchers, leadership, and System Council. The main benefit is an assurance that the best possible science is conducted to deliver the intended development outcomes. The reviews aim to guide funders’ investments in CGIAR research, ensuring they are well targeted and likely to succeed. They are designed to help CGIAR leadership and scientists to improve the structure and content of their research that delivers real outcomes and impact.